The Importance of Carbapenemase-Producing Enterobacterales in African Countries: Evolution and Current Burden - Edgar-Costin Chelaru; Andrei-Alexandru Muntean; Mihai-Octav Hogea; Mădălina-Maria Muntean; Mircea-Ioan Popa; Gabriela-Loredana Popa (MDPI AG, 2024)
Antimicrobial resistance (AMR) is a worldwide healthcare problem. Multidrug-resistant organisms (MDROs) can spread quickly owing to their resistance mechanisms. Although colonized individuals are crucial for MDRO dissemination, colonizing microbes can lead to symptomatic infections in carriers. Carbapenemase-producing Enterobacterales (CPE) are among the most important MDROs involved in colonizations and infections with severe outcomes. This review aimed to track down the first reports of CPE in Africa, describe their dissemination throughout African countries and summarize the current status of CRE and CPE data, highlighting current knowledge and limitations of reported data. Two database queries were undertaken using Medical Subject Headings (MeSH), employing relevant keywords to identify articles that had as their topics beta-lactamases, carbapenemases and carbapenem resistance pertaining to Africa or African regions and countries. The first information on CPE could be traced back to the mid-2000s, but data for many African countries were established after 2015-2018. Information is presented chronologically for each country. Although no clear conclusions could be drawn for some countries, it was observed that CPE infections and colonizations are present in most African countries and that carbapenem-resistance levels are rising. The most common CPE involved are Klebsiella pneumoniae and Escherichia coli, and the most prevalent carbapenemases are NDM-type and OXA-48-type enzymes. Prophylactic measures, such as screening, are required to combat this phenomenon.